2013
DOI: 10.1039/c2cs35263j
|View full text |Cite
|
Sign up to set email alerts
|

Medium and high oxidation state metal/non-metal fluoride and oxide–fluoride complexes with neutral donor ligands

Abstract: While most high and medium oxidation state (O.S. ≥ 3) metal and non-metal fluorides and oxide fluorides are strong Lewis acids, exploration of their coordination chemistry with neutral ligands has been limited and mostly non-systematic. This is despite the very different properties conferred on the acceptor centre by the small electronegative fluoride ligands compared to the heavier halides. This article sets out these key differences, discusses possible synthetic routes, the key characterisation techniques, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 367 publications
(444 reference statements)
2
107
0
Order By: Relevance
“…As discussed for aluminium (Section 6.2), other factors sometimes complicate interpretation of Lewis acidity based upon bond length data, but it seems clear in the case of gallium(III) that, apart from a few anomalies, the data indicate an order with halide Cl > Br > I [131,170,171]. Analogous to the aluminium system, GaF 3 is an inert polymer and no soft donor complexes are known [130]. For neutral phosphines and arsines, the gallium(III) overwhelmingly favours distorted tetrahedral four-coordination, and six-coordination is achieved only in some chelating diphosphine adducts.…”
Section: Galliummentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed for aluminium (Section 6.2), other factors sometimes complicate interpretation of Lewis acidity based upon bond length data, but it seems clear in the case of gallium(III) that, apart from a few anomalies, the data indicate an order with halide Cl > Br > I [131,170,171]. Analogous to the aluminium system, GaF 3 is an inert polymer and no soft donor complexes are known [130]. For neutral phosphines and arsines, the gallium(III) overwhelmingly favours distorted tetrahedral four-coordination, and six-coordination is achieved only in some chelating diphosphine adducts.…”
Section: Galliummentioning
confidence: 99%
“…Whilst tetrahedral four coordination is still the norm, five-or six-coordination is found in some aluminium complexes. Very few complexes (none with soft donors) are known for AlF 3 , which unlike the molecular BF 3 is an inert fluorine-bridged polymer [130]. Monodentate ER 3 adducts of AlR 3 (R = alkyl) have been thoroughly investigated, but detailed studies of complexes of AlX 3 are surprisingly rare and complexes with bi-and polydentates have received very limited study.…”
Section: Aluminiummentioning
confidence: 99%
See 1 more Smart Citation
“…Although their study was neglected for many years, recent work has revealed an extensive coordination chemistry of early transition metal fluorides, including TiF 4 , ZrF 4 , HfF 4 , NbF 5 , TaF 5 and WF 6 [1]. In marked contrast, the coordination chemistry of lanthanide fluorides is limited to a range of fluorometallate anions, and a few, usually poorly characterised hydrates [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Many fluoride complexes of this type are described in the literature [6]. The chemistry and structure of p-, d-, and f-block metal fluoride and oxofluoride complexes with neutral donor ligands, including TiF 4 complexes with O-and N-donor ligands, were systematized by Benjamin et al [10].…”
Section: Introductionmentioning
confidence: 99%